2010
DOI: 10.1016/j.trstmh.2010.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent preventive treatment of malaria in pregnancy (IPTp): do frequent antenatal care visits ensure access and compliance to IPTp in Ugandan rural communities?

Abstract: The relationship between antenatal care (ANC) visits and coverage of intermittent preventive treatment of malaria in pregnancy (IPTp) with sulfadoxine-pyrimethamine (SP), and barriers to IPTp-SP access were examined. Four hundred and fifty-three women who had given birth during the study period were interviewed using a semi-structured questionnaire. Of these, 425 (93.8%) attended ANC at least once, but only 90 (21.2%) made four or more visits. Primigravidae 25 (29.8%) were more likely than multigravidae 65 (17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
30
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 16 publications
6
30
1
Order By: Relevance
“…In addition, multigravidae were more knowledgeable than primigravidae women regarding IPT. Similar to the findings of this study, other studies have also reported that age of the pregnant woman, time of registration with an antenatal provider, gravida and transport facilities available in the village were important predictors significantly affecting the utilization of minimum recommended antenatal care services [9,10]. These results indicate the need to have sensitization programs that that are designed to target different groups of pregnant women at the antenatal clinics.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In addition, multigravidae were more knowledgeable than primigravidae women regarding IPT. Similar to the findings of this study, other studies have also reported that age of the pregnant woman, time of registration with an antenatal provider, gravida and transport facilities available in the village were important predictors significantly affecting the utilization of minimum recommended antenatal care services [9,10]. These results indicate the need to have sensitization programs that that are designed to target different groups of pregnant women at the antenatal clinics.…”
Section: Discussionsupporting
confidence: 88%
“…Because of late and irregular attendance to antenatal clinics, a large number of pregnant women did not receive the recommended two doses of SP for IPT at the pre-determined times. A similar study that was conducted in Uganda in 2010 also indicated that late and irregular attendance to antenatal clinics disrupt antenatal schedules for proper delivery of IPT [9]. In the present study, pregnant women who had attended antenatal clinics for at least 3 times had better knowledge on IPT policy compared to those who had attended once or twice, suggesting an association between the number of antenatal visits and the level of knowledge on IPT policy among pregnant women.…”
Section: Discussionsupporting
confidence: 67%
“…20 The pattern of ANC visits in this study is very similar to what has been reported in other studies in the country and in the subregion. 21,22 This low turnout for ANC visits by pregnant women implies that the majority of pregnant women that registered in health care facilities in the state do not get the full benefit of ANC services; they probably deliver their babies in nonformal health facilities and are therefore at high risk of negative pregnancy outcomes.…”
Section: Utilization Of Anc and Iptpmentioning
confidence: 99%
“…These are chemoprophylaxis using sulfadoxinepyrimethamine (SP) and insecticide treated net (ITN) 3 . However non adherence to chemoprophylaxis, irregular, late or non antenatal clinic attendance, women not given Intermittent Presumptive Treatment (IPT) by midwife and drug stock outs in most health facilities in Uganda is common 10 . These problems would not be encountered by pregnant women who own an ITN and thus making ITN more effective mean of malaria prevention in Uganda among pregnant women.…”
Section: Introductionmentioning
confidence: 99%